Influence of diabetes mellitus on inflammatory bowel disease course and treatment outcomes. A systematic review with meta-analysis. Issue 5 (May 2023) - Fuschillo, Giacomo; Celentano, Valerio; Rottoli, Matteo; Sciaudone, Guido; Gravina, Antonietta Gerarda; Pellegrino, Raffaele; Marfella, Raffaele; Romano, Marco; Selvaggi, Francesco; Pellino, Gianluca
Abstract: Background: Diabetes Mellitus (DM) may occur in IBD and influence the disease progression. Aim: To compare disease course and treatment outcomes in IBD patients with and without DM. Methods: This is a systematic review with meta-analysis comparing patients with IBD plus DM with patients with IBD only. Primary endpoints: need for surgery, IBD-related complications, hospitalizations, sepsis, mortality. Quality of life and costs were assessed. Results: Five studies with 71, 216 patients (49.1% with DM) were included. Risk for IBD-related complications (OR=1.12, I 2 98% p  = 0.77), mortality (OR=1.52, I 2 98% p  = 0.37) and IBD-related surgery (OR=1.20, I 2 81% p  = 0.26) did not differ. Risk of IBD-related hospitalizations (OR=2.52, I 2 0% p  < 0.00001) and sepsis (OR=1.56, I 2 88% p  = 0.0003) was higher in the IBD+DM group. Risk of pneumonia and urinary tract infections was higher in the IBD+DM group (OR=1.72 and OR=1.93), while risk of C. Difficile infection did not differ (OR=1.22 I 2 88% p  = 0.37). Mean Short Inflammatory Bowel Disease Questionnaire score was lower in the IBD+DM group (38.9 vs. 47, p  = 0.03). Mean health care costs per year were $10, 598.2 vs $3747.3 ( p  < 0.001). Conclusion: DM might negatively affect the course of IBD by increasing the risk of hospitalization and infections, but not IBD-related complications and mortality.